2016
DOI: 10.1177/0256090916663390
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Response of Consumers with Different Levels of Uniqueness to Limited Quantity Offers

Abstract: includes research articles that focus on the analysis and resolution of managerial and academic issues based on analytical and empirical or case researchMarketers try to influence consumers through promotional offers by restricting availability of products to a limited number of customers, a limited time period, or a specific segment, thereby creating a perception of scarcity. Such promotional appeal of making a product or offer scarce is called as scarcity appeal.Literature suggests that people with high need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The more unique the company's product, the more the consumer put interest on it, so it will increase sales and finally will increase profitability. This research result supports the study conducted by Cheema and Kaikati (2010) and Soni and Koshy (2016), who find the uniqueness of a product will increase purchase intention.…”
Section: Empirical Results and Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The more unique the company's product, the more the consumer put interest on it, so it will increase sales and finally will increase profitability. This research result supports the study conducted by Cheema and Kaikati (2010) and Soni and Koshy (2016), who find the uniqueness of a product will increase purchase intention.…”
Section: Empirical Results and Analysissupporting
confidence: 89%
“…The more unique a product, the more consumer put interest in it to increase the possibility to buy it (Cheema and Kaikati, 2010). A consumer with a high need for uniqueness tends to increase purchase intention (Soni and Koshy, 2016). This means a unique product will increase consumer's intention to buy.…”
Section: Uniqueness (X 7 )mentioning
confidence: 99%
“…Meanwhile, a research conducted by Cheema and Kaikati (2010) found that the more unique a product is, it will be more demanded by consumers and as a result, purchase experiences an increase. Consumers who have high need for uniqueness will increase their purchase intention (Soni and Koshy, 2016). This means uniqueness has a positive effect on profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when comparing consumers by personal control, those with low personal control had greater intention to purchase when exposed to the low-stock scarcity message while those with high personal control had no intentions to purchase when exposed to the low-stock scarcity message (Lee et al, 2018). A study with print advertisements for laptops found that a low-stock scarcity message was associated with greater positive attitudes and greater purchase intention than an advertisement with no lowstock scarcity message (Soni and Koshy, 2016). A survey of consumers about limitedquantity electronic games found that perceived scarcity was positively associated with perceived uniqueness and perceived quality which was then positively associated with perceived value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2018). A study with print advertisements for laptops found that a low-stock scarcity message was associated with greater positive attitudes and greater purchase intention than an advertisement with no low-stock scarcity message (Soni and Koshy, 2016). A survey of consumers about limited-quantity electronic games found that perceived scarcity was positively associated with perceived uniqueness and perceived quality which was then positively associated with perceived value.…”
Section: Introductionmentioning
confidence: 99%